1999
DOI: 10.1097/00003246-199909000-00047
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating palliative care into critical care education: Principles, challenges, and opportunities

Abstract: Teaching care of the dying in the ICU should emphasize the following: a) the goals of care should guide the use of technology; b) understanding of prognostication and treatment withholding and withdrawal is essential; c) effective communication and trusting relationships are crucial to good care; d) cultural differences should be acknowledged and respected; and e) the delivery of excellent palliative care is appropriate and necessary when patients die in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
8

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 33 publications
0
61
0
8
Order By: Relevance
“…3-6,10,16,29 -32 This survey revealed that with the exception of 1 case, the physician responsible for writing DNR orders was actually the intensivist, frequently a stranger to the families, rather than the child's referring physician. 7,[33][34][35] The patients in the study who had LST forgone were older and had a longer PICU stay. 11 The end-of-life process more frequently involved LST removal, because only 18% (7 of 39) of the W/LT group had limitation or no escalation of therapy as the mode of choice.…”
Section: Modes and Time Of Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…3-6,10,16,29 -32 This survey revealed that with the exception of 1 case, the physician responsible for writing DNR orders was actually the intensivist, frequently a stranger to the families, rather than the child's referring physician. 7,[33][34][35] The patients in the study who had LST forgone were older and had a longer PICU stay. 11 The end-of-life process more frequently involved LST removal, because only 18% (7 of 39) of the W/LT group had limitation or no escalation of therapy as the mode of choice.…”
Section: Modes and Time Of Deathmentioning
confidence: 99%
“…43 Our survey clearly demonstrated that decision making at the end of life in the PICU is a dynamic process. 31,33,37,39,44 In almost half of the W/LT group, limitation in the level of support was considered in the earlier stages. Subsequently, 1 or more modes of LST were actually withdrawn.…”
Section: Why and How Decisions Are Madementioning
confidence: 99%
See 1 more Smart Citation
“…49 Outside of Canada there is a body of evidence to suggest that end of life care in the ICU falls short of these standards, leading to calls for better palliation. 50,51 The situation in Canada appears more encouraging with families reporting that most patients die in comfort in the ICU 17 and that the families themselves feel supported during the dying process. 37 However, inconsistencies in end of life care practices may affect where patients die, how they die, the quality of that death 52,53 and whether or not patients are considered for organ and tissue donation in the ICU.…”
Section: Withdrawal Of Mechanical Ventilationmentioning
confidence: 99%
“…1 Subsequently there have been many calls for better defined goals for, and better care of, dying patients in the intensive care units (ICUs). [2][3][4][5][6][7] Improvements to care in the ICU could take many forms: attention to communication strategies, better understanding of cultural issues, use of ethical committees in difficult cases or process issues within the ICU to improve consistency in care delivery. Regarding consistency, we recently reported tenfold variations in prescribed doses of morphine during the last 12 hr of life in dying ICU patients.…”
Section: Conclusion : Des Changements Simples Au Processus De Rmfv Pementioning
confidence: 99%